La peinture à vue de nez ou la juste distance du critique d’art, de Diderot à Zola - Wicky, Érika (RACAR : Revue d'art canadienne / Canadian Art Review)

(untitled) (UAAC-AAUC (University Art Association of Canada | Association d'art des universités du Canada), 2014)
Since the emergence of exhibition practices in the eighteenth and nineteenth centuries, there has been a progressive normalization of the material conditions for observing paintings, such as their placement and the spectator’s distance to them. Just like painters and Salon visitors, art critics needed to move closer to their object of inquiry in order to gain better knowledge of it, but paradoxically, they could not claim objectivity without stepping back. The ideal distance that would allow viewers to simultaneously grasp the whole and the details was a contentious topic of discussion for nineteenth-century artists, critics, and scientists. Among the different ways in which this question was formulated in art criticism, one in particular reveals the presuppositions of the time about proximity: the constant reference to the smell of the painting. Associated with proximity, smell metaphorizes the pleasure or trouble spectators feel when they get close to paintings, to their pictorial materiality, or even to the figures depicted. Because smell always functions as a sign of the substance from which it emanates, art critics’ reference to it allowed them to consider the problem of proximity within the social and aesthetic issues of their time.